Analysis of 2011 physician assistant education debt load. Issue 3 (March 2017) - Moore, Miranda A.; Coffman, Megan; Cawley, James F.; Crowley, Diana; Miller, Anthony; Klink, Kathleen
Abstract : ABSTRACT: This study seeks to investigate how physician assistants (PAs) finance their education and to characterize the educational debt of PA students. Data from the 2011 American Academy of PAs (AAPA)–Physician Assistant Education Association Graduating Student Survey were used to explore the educational debt of PA students. The median total educational debt of a PA student graduating in 2011 was 80, 000. Little financial assistance, other than student loans, is available to PA students. Eighty-five percent of PA students report owing some PA education debt amount, with 23% owing at least 100, 000. This study provides a baseline look at PA student debt loads as a starting point for more detailed and robust research into new graduate specialty choices and PA career migration into other specialties. Further research is needed to explore the effect of student debt on students' specialty choices.